Study of fatigue damage of pumping rods based on finite element simulation - Cai, Wenbin; Mo, Xiangyang; Li, Wen; Liu, Shun; Zhou, Desheng; Zhang, Huiren; Huang, Zhimin (Frontiers in Earth Science, 2023)
This study performed in-depth analysis of onsite fatigue damage and stress distribution in pumping rods. Two aspects of fatigue damage were analyzed: macroscopic morphology and chemical properties. In terms of chemical properties, the crystalline phase composition and hardness of the product at fatigue damage were analyzed; the stress distribution was analyzed in term so of the rod-body stress and the connection-section stress. The cross-sectional characteristics of the fatigue crack expansion were summarized, and the types of fatigue fracture and the influencing factors of the pumping rod were obtained from these cross-sectional characteristics. Finally, modeling and stress analysis of the pumping rod were performed using SolidWorks and ABAQUS software. By comparing the stress cloud diagrams of different thread root shapes, the factors that cause fracture in the pumping rod and the locations of stress concentrations and dangerous cross-sections of the rod were determined. The highest principal stresses were obtained at the rod body near the upsetting flange of the pumping rod, and fatigue damage was the most likely to occur at this location. The shoulder of the unloading groove and the upsetting flange area were relatively safe because of their large cross-sectional area and less likelihood to produce stress concentrations. The results of this study can provide scientific guidance and reference for the development of pumping rods for efficient oil production and the improvement of oil and gas production efficiency.